Some features of the competitive relations in high school - E. S. Kushel’ (Известия высших учебных заведений: Геология и разведка, 2017)
An analysis of the competitiveness of the high school is considered as a patch of the subsystems, which level of development determines its competitive advantages. The subsystems have been distinguished: basic high school activity, additional high school activity, providing high school activity.